2007
DOI: 10.1016/j.ijrobp.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients With Locally Advanced Prostate Cancer After 76 Gy Intensity-Modulated Radiotherapy vs. 70 Gy Conformal Radiotherapy in a Prospective and Longitudinal Study

Abstract: Purpose: To compare quality of life (QoL) after 70 Gy conformal radiotherapy with QoL after 76 Gy intensitymodulated radiotherapy (IMRT) in patients with locally advanced prostate carcinoma. Methods and Materials: Seventy-eight patients with locally advanced prostate cancer were treated with 70 Gy three-field conformal radiotherapy, and 92 patients received 76 Gy IMRT with fiducial markers for position verification. Quality of life was measured by RAND-36, the European Organization for Research and Treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 28 publications
9
52
1
1
Order By: Relevance
“…Published comparisons of conventional and hypofractionated radiation schedules for the treatment of prostate cancer indicate that recurrence-free survival is equal or improved with hypofractionation [21][22][23] . Those studies also showed that the qol of prostate cancer patients is either similar or better with the hypofractionated schedules [24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Published comparisons of conventional and hypofractionated radiation schedules for the treatment of prostate cancer indicate that recurrence-free survival is equal or improved with hypofractionation [21][22][23] . Those studies also showed that the qol of prostate cancer patients is either similar or better with the hypofractionated schedules [24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…The 1-and 6-month follow-up was based on the scoring system described ( Table i). The qol scores for each of the 18 items for each follow-up point (1,6,12,18,24,30, and 36 months) were compared with the baseline scores using the generalized estimating equation approach 33 . That approach accounts for the within-subject correlations arising because of repeated measurements of the same individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IMRT ile de geçici yan etkilerin görülebileceği çeşitli çalışmalarla bildirilmiştir. [18,19] Yoğunluk ayarlı radyoterapi sonrası grad 2 ve üzeri üriner yan etki yaklaşık %30-40 oranında gö-rülmektedir [18,20] . Gİ yan etkiler ise De Meerleer ve ark.…”
Section: Discussionunclassified